Burden of Pediatric Cancer Treatment: Results of Online Pediatric Cancer Registry Prototype 1 at A Third Referral Hospital in Indonesia - Sari, Nur Melani; Reniarti, Lelani; Suryawan, Nur; Susanah, Susi; Wahyudi, Kurnia (Althea Medical Journal, 2017)
Background: Despite the impressive progress of high-income countries, childhood cancer survival remains low in low and middle-income countries. Cancer is yet to be considered as a significant public health issue which has implicate only few pediatric cancer registry has been well established. The study aimed to describe the burden of pediatric cancer treatment in a third referral hospital in Indonesia through pediatric cancer registry.Methods: A-three-year retrospective analysis of 15 pediatric cancer diagnosed in children aged under 14 years was conducted at Dr Hasan Sadikin General Hospital, Bandung.Â  Data were extracted from Online Bandung Pediatric Cancer Registry Prototype 1 and analyzed for age, gender, type of cancer. The outcomes were classified as treatment abandonment, treatment refusal, interrupted treatment, death during treatment, and completed treatment.Results: Seven-hundred and seventy-three children, 452 males and 321 females, were diagnosed with 15 types of malignancies.Â  Peak incidence for each malignancy was different: at a young age was found in retinoblastoma and hepatoblastoma (mean; 3yo) while at adolescence in bone tumor and chronic myelocytic leukemia (9.1; 10 yo respectively). Distribution of the foremost malignancies recorded was: acute lymphoblastic leukemia (44.5%), retinoblastoma (15.2%), and non-Hodgkin lymphoma (8.9%). The cancer cure rate was very low (9.5%), treatment abandonment was still high (41.7%) and most patients died (27.8%) in the course of therapy either from advanced disease, infection, or late presentation. Meanwhile, 167 patients still continued the interrupted treatment.Conclusions: Cancer management is the burden for hospital, however the general outcome is very poor.Â